Syngas Production Through H2O/CO2 Thermochemical Splitting Over Doped Ceria-Zirconia Materials - Luciani, Giuseppina; Landi, Gianluca; Di Benedetto, Almerinda (Frontiers in Energy Research, 2020)
This study investigates the catalytic properties of K+ and Cu2 + /Fe3 + co-doped ceria-zirconia (CeZr) toward water and carbon dioxide co-splitting. These materials can convert separate feeds of CO2 and H2O into CO and H2. In co-splitting tests, water reacts faster on the K-Cu-CeZr catalyst with negligible CO production. The reduction of the K-Fe-CeZr catalyst occurs over two broad temperature ranges: at low temperature, only H2 is produced; whereas CO is the most abundant product at high temperature. A kinetic model was developed to get insights into the reasons of the observed selectivity toward H2 at low temperature and CO at a higher temperature. The different reaction orders in the sites fraction were evaluated for CO2 and H2O reactions, highlighting that H2 production requires a larger number of adjacent reduced sites than CO production. Three regimes were identified through the model: Regime I- H2O driven regime @T ≤ 650°C; Regime II- mixed regime @ 560 < T < 700°C and Regime III: CO2 driven regime @ T > 700°C. These results indicate the appropriate conditions for tuning H2/CO selectivity, depending on the feed composition.